Electrochemical Pretreatment of Solid–Electrolyte Interphase Formation for Enhanced Li4Ti5O12 Anode Performance in a Molten Li–Ca Binary Salt Hydrate Electrolyte. Issue 11 (6th May 2022) - Kondou, Shinji; Watanabe, Yoshifumi; Dokko, Kaoru; Watanabe, Masayoshi; Ueno, Kazuhide
Abstract: Invited for this month's cover picture is the group of Prof. Kazuhide Ueno from Yokohama National University (Japan). The cover picture illustrates that less‐water‐soluble Ca‐based solid electrolyte interphase formed in a Li–Ca binary salt hydrate electrolyte effectively mitigates electrochemical reduction of water, leading to improvement in the cycle performance of a Li4 Ti5 O12 electrode. Read the full text of the Research Article at 10.1002/celc.202200061 . Abstract : "Significant improvement in the cycle performance of a Li4 Ti5 O12 electrode was achieved using a Li–Ca binary salt hydrate (LCH) electrolyte in combination with an optimized electrochemical pretreatment process. The LCH electrolyte provided less‐water‐soluble Ca‐based SEI components, and careful pretreatment process enabled the formation of a thicker SEI layer on the Li4 Ti5 O12 electrode, leading to 95.5 % capacity retention over 50 cycles…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Research Article at 10.1002/celc.202200061 .